PROSES KOORDINASI KETERTIBAN UMUM DI KELURAHAN SIANTAN HILIR KECAMATAN PONTIANAK UTARA - Chahyadi E.01108020, Dwi (FISIP Universitas Tanjungpura, 2013)
The title of this article is the Public Order Process Coordination in Lower Village District Siantan North Pontianak. This article dilator background by the number of buildings on land that is not in accordance with the functions and use established by the conduct trades for their subsistence and aim to gain employment with limited land, this is usually as practiced by the merchants sidewalk or commonly refer to as street vendors. Formulation of the problem in this article, namely:'' How the Process Implementation Coordinating Public Order law in village district Siantan Lower North Pontianak